Reading comprehension treatment in aphasia: A systematic review - Purdy, Mary; Coppens, Patrick; Madden, Elizabeth Brookshire; Mozeiko, Jennifer; Patterson, Janet; Wallace, Sarah E.; Freed, Donald (Aphasiology, 2019)
Background: Reading difficulties often present as a consequence of aphasia. The specific nature of reading deficits varies widely in manifestation, and the cause of these deficits may be the result of a phonological, lexical semantic, or cognitive impairment. Several treatments have been developed to address a range of impairments underlying reading difficulty.Aims: The purpose of this review is to describe the current research on reading comprehension treatments for persons with aphasia, assess the quality of the research, and summarize treatment outcomes.Methods & Procedures: A systematic review of the literature was conducted based on a set of a priori questions, inclusion/exclusion criteria, and pre-determined search parameters. Results were summarized according to treatment type, methodologic rigor, and outcomes.Outcomes & Results: Fifteen studies meeting criteria were identified. A variety of reading comprehension treatments was implemented including: oral reading, strategy-based, cognitive treatment, and hierarchical reading treatments. Quality ratings were highly variable, ranging from 3 to 9 (on a 12-point scale). Overall, 14 of the 18 individuals for whom individual data were provided demonstrated some degree of improvement (oral reading 4/5 participants, strategy based 4/6, and cognitive treatment 6/7). Gains were also evident for hierarchical reading treatment administered to participant groups via computer; however, the degree to which improvement reached statistical significance varied among studies.Conclusions: Reading comprehension treatments have the potential to improve reading comprehension ability in persons with aphasia; however, outcomes were variable within and among treatment methods. We suggest focusing future research on factors such as participant candidacy and treatment intensity using increased methodological rigor.
Keywords: Aphasia; Mini Mental State Examination; Review; agraphia; aphasia; certification; cognition; cognitive defect; communication skill; comprehension; deep learning; dementia; dept.cmd; dyslexia; episodic memory; human; interrater reliability; language test; motivation; peer-reviewed; phonetics; psychometry; quality of life; randomized controlled trial (topic); reading; reading comprehension; scientific literature; social hierarchy; stamen; systematic review; treatment; treatment outcome; word recognition; working memory

Generalization in aphasia treatment: a tutorial for speech-language pathologists - Mayer, Jamie F.; Madden, Elizabeth B.; Mozeiko, Jennifer; Murray, Laura L.; Patterson, Janet P.; Purdy, Mary; Sandberg, Chaleece W.; Wallace, Sarah E. (American Journal of Speech-Language Pathology, 2024)
Purpose: Generalization has been defined and instantiated in a variety of ways over the last half-century, and this lack of consistency has created challenges for speech-language pathologists to plan for, implement, and measure generalization in aphasia treatment protocols. This tutorial provides an overview of generalization with a focus on how it relates to aphasia intervention, including a synthesis of existing principles of generalization and examples of how these can be embedded in approaches to aphasia treatment in clinical and research settings. Method: Three articles collectively listing 20 principles of generalization formed the foundation for this tutorial. The seminal work of Stokes and Baer (1977) focused attention on generalization in behavioral change following treatment. Two aphasia-specific resources identified principles of generalization in relation to aphasia treatment (Coppens & Patterson, 2018; Thompson, 1989). A selective literature review was conducted to identify evidence-based examples of each of these 20 principles from the extant literature. Results: Five principles of generalization were synthesized from the original list of 20. Each principle was supported by studies drawn from the aphasia treatment literature to exemplify its application. Conclusions: Generalization is an essential aspect of meaningful aphasia intervention. Successful generalization requires the same dedication to strategic planning and outcome measurement as the direct training aspect of intervention. Although not all people with aphasia are likely to benefit equally from each of the principles reviewed herein, our synthesis provides information to consider for maximizing generalization of aphasia treatment outcomes. Supplemental Material: https://doi.org/10.23641/asha.24714399
Keywords: dept.cmd; peer-reviewed